Patient experiences of recovery after heart valve replacement: suffering weakness, struggling to resume normality - Berg, Selina Kikkenborg (BioMed Central, 2013)
BACKGROUND: Heart valve disease is becoming a public health problem due to increasing life expectancy and new treatment methods. Patients are at risk of developing depression, anxiety or post-traumatic stress disorder after heart valve surgery. To better plan proper care, describing and understanding patients’ perception of recovery after heart valve replacement is essential. The objective was to describe the experience of recovery at home after heart valve replacement. METHODS: Qualitative interviews were conducted with 10 patients representing the population and these were later transcribed. The analysis was inspired by Ricoeur’s theory of interpretation, which consists of three levels: naive reading, structured analysis, and critical interpretation and discussion. RESULTS: The overall concept that emerged was suffering weakness and struggling to resume normality. Patients all struggled to resume normal living, both in regaining physical strength and in reestablishing balance in overall living. The overall concept can be interpreted in terms of the following themes: Disturbed network: Invaluable relatives, Contact with healthcare staff, Rehabilitation. Disturbed body: Stressful complications, Bodily attention, Physically affected, Physical capability. Recovery: Interrupted living, Suffering weakness, Gradual recovery, Achieving normality. Reflections: Thoughts about the procedure and Feeling sad and fragile. CONCLUSION: The study presents the main themes of network, body, recovery and reflection for ten patients after heart valve replacement. These main themes can overall be summarized as suffering weakness and struggling to resume normality. Patients felt weak with a changed body, but after a long recovery process regained vitality and returned to their daily life.